KEKERASAN TERHADAP ANAK DITINJAU DARI ASPEK KRIMINOLOGI DIKAITKAN DENGAN UNDANG-UNDANG HAM (Studi Kasus Putusan Nomor : 1.141/Pid.B.2011/PN.Mdn) - Suhatrizal, Suhatrizal; Wahyuni, Windy Sri; Ibrahim, Ahmad (Jurnal Ilmiah Penegakan Hukum, 2014)
The law provides for the protection of children who receivedomestic violence by asking legal liability to the perpetrators of crimes ofviolence against children. Legal liability of actors give due to theperpetrators may be subject to criminal sanction in the form ofimprisonment or fine or both at once.